Innovative marketing and sales promotion: catalysts or inhibitors of SME performance in Ghana - Karikari Amoa-Gyarteng; Shepherd Dhliwayo; Victoria Adekomaya (Cogent Business & Management, 2024)
Innovative marketing (IM) drives success in small and medium enterprises (SMEs); however, the impact of sales promotions (SPs) remains a double-edged sword. This is the crux of this study, which examines the influence of IM and SP on SME performance in Ghana. Hierarchical regression analysis tested the hypotheses using a sample of SMEs registered with the Ghana Enterprises Agency. The results indicated a significant positive association between IM practices and SME performance. Contrary to expectations, SP exhibited a statistically significant negative association with SME performance. In addition, SP moderates the IM -performance link. The practical implication is that Ghanaian SMEs should synergistically integrate SPs and IM practices. This study addresses the pressing need for entrepreneurial marketing research grounded in the nuances of African economies, enriching the scholarly landscape.
Keywords: 650; SME performance; innovative marketing; sales promotion; diffusion of innovation theory; promotional mix theory; entrepreneurship